Evaluation of Secondary Schools Students' Exposure to Risk Factors in Al-Najaf City - Ghyadh, ali; Abdul-Wahid, hala (Iraqi National Journal of Nursing Specialties, 2016)
Objective: The study aim to evaluate secondary schools students' exposure to risk factors in Al-Najaf City. Methodology: Descriptive study conducted in Al- Najaf City/Iraq on students at secondary schools, those aged (12-24) years old, for the period from the 13ed of November 2015 and up to 4ed of August 2015. The sample included secondary school from those schools . Data is collected through a constructed questionnaire, reliability and students (intermediate and secondary) (540) student; (270) male and (270) females who are selected randomly content validity process has been determined for the instrument. Data is analyzed by using of descriptive and inferential data analysis methods. Results: The findings of the study present that secondary schools students are exposed to risk factors with high significant , numerous risks directly linked to their behavior , their families , their schools and to their community . Recommendations: The study recommends to emphasis on the need for the cooperation between the Ministry of Health and the Ministry of Education on plans for the wellbeing of students and protection from risk behaviors and provision of adequate support and guidance , and emphasis on the role of parents in protecting their children through educating them by a guidance programs.